Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) Mid-year report 2025 - Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The 2025 mid‑year report for the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project under its Additional Financing (AF) phase showcases continued progress toward achieving all five Project Development Objectives (PDOs) of the project. As the final year of AICCRA’s current implementation phase, 2025 marks a critical moment in the program’s journey, laying a strong foundation to support the anticipated third phase of the program, which will introduce a new focus, expanded scope, and changing operational elements. Therefore, as a transition year, 2025 is witnessing the AICCRA team keeping itself well aligned with the goals committed under the Additional Financing phase, while also investing efforts to contribute effectively to the design phase of AICCRA III, based on the successes and challenges of the last years, adopting lessons learned and possible solutions.